Comparison of EuroQol-5D-3L and Short Form-6D Utility Scores in Family Caregivers of Colorectal Cancer Patients: A Cross-Sectional Survey in China - Sun, Cheng-yao; Liu, Yang; Zhou, Liang-ru; Wang, Ming-si; Zhao, Xian-ming; Huang, Wei-dong; Liu, Guo-xiang; Zhang, Xin (Frontiers in Public Health, 2021)
Objective: To compare the EuroQol-5D-3L (EQ-5D-3L) and the Short Form-6D (SF-6D) utility scores in family caregivers (FCs) of colorectal cancer (CRC) patients. Method: This study was performed on FCs of CRC patients from three primary cancer centers in the capital city of the Heilongjiang province. The participants (FCs) who were enrolled, filled the EQ-5D-3L, along with the SF-6D questionnaire. Two tools were compared for their distribution, discriminant validity, agreement, and convergent validity along with known-groups validity. Result: Two hundred ninety-two FCs of CRC patients were enrolled. The score distribution of the SF-6D along with the EQ-5D-3L were not normal. A ceiling impact was seen in 31.8% of the FCs for EQ-5D-3L; however, none for the SF-6D. Good associations (Spearman’s rho = 0.622, p < 0.01) and intraclass correlation coefficient (ICC 0.637 and average ICC 0.778) between the two scores were observed. The EQ-5D-3L yielded higher utility scores in contrast with the SF-6D in the better health subclass. The SF-6D distinguished better between excellent and good health statuses, with better effect size and relative efficiency statistics. Both tools showed good known-groups validity. Conclusion: The utility scores of SF-6D were remarkably lower relative to that of the EQ-5D-3L, but the difference may be clinically insignificant. However, the SF-6D may be superior because of the lack of ceiling impact. SF-6D exhibited a better convergent validity along with discrimination validity of excellent health condition and improved known-groups validity efficiency.